A2 Adenosine Receptor-mediated Cardioprotection Against Reperfusion Injury in Rat Hearts Is Associated With Autophagy Downregulation. Issue 1 (July 2015) - Ke, Jianjuan; Yao, Bo; Li, Tao; Cui, Shanshan; Ding, Huang
Abstract : Abstract: This study was undertaken to determine and confer the cardioprotective effects of the adenosine A2 receptor (A2AR) and its impact on myocardial autophagy in the setting of reperfusion. We established a rat ischemia model by subjecting rats to 30 minutes of ischemia (I) and 120 minutes of reperfusion (R). The A2AR agonists CGS21680 (A2aAR specific) and BAY60-6583 (A2bAR specific) were administered separately and in combination 5 minutes before reperfusion (postconditioning). No visible improvements in the rats' hemodynamic changes in response to either CGS or BAY were observed compared with untreated control groups (I/R). BAY significantly reduced infarct sizes, whereas CGS did not. Electron microscopy, enzyme-linked immunosorbent assay and TUNEL apoptosis staining results demonstrated that CGS and BAY play cardioprotective roles by maintaining mitochondria structural stability, decreasing serum cardiac troponin I (cTnI) concentrations and decreasing the number of apoptotic cells. CGS21680 and BAY60-6583 slightly increased the expression (vs. I/R group) of Bcl-2 and significantly attenuated the expression of Beclin-1, LC3B, and LAMP-2, as analyzed by Western blot, compared with the I/R alone group. Notably, BAY60-6583 exerts a predominant effect on mitochondria structural stabilization, apoptotic inhibition, and attenuation of LC3B/LAMP-2 expression. No synergistic effects were observed for the 2 agonists. Our data suggest that A2AR-mediated cardioprotection is associated with Beclin-1–induced autophagy downregulation in the setting of reperfusion. A2bAR activation exerts stronger cardioprotective effects against I/R injury compared with A2aAR.